Exit-site fungal infections: experience of a Peritoneal Dialysis Unit - Coelho,Sofia (2016)
Introduction: Exit-site infections are an important complication of peritoneal dialysis; however, very little is known about fungi-related exit-site infections. The literature is very sparse and there are virtually no studies that report it. Objective: To evaluate in retrospect the risk factors associated with exit-site fungal infection and its development. Methods: The study included all diagnosed episodes of exit- site fungal infections in patients undergoing peritoneal dialysis in a hospital unit between 2011 and 2014, analyzed in relation to demographic, clinical and analytical variables. Results: The studied group included 26 patients, 70% of which were female, with a median age of 54 years old; average length in PD treatment three years. The majority of patients (70%) were undergoing manual peritoneal dialysis. About 30 episodes of exit-site fungal infections were diagnosed during the follow-up period, which corresponded to 5.6% of total exit-site infections diagnosed. About 23% of patients suffered from diabetes mellitus and 13% had undergone immunosuppressive therapy in the six months previous to the episode. Two thirds of patients (n=20) had undergone antibiotherapy in the previous three months, the majority (65%) for the treatment of peritoneal dialysis-related infection and 46% of these patients underwent concomitant antifungal prophylaxis with fluconazole. The exit-site fungal infections were predominantly caused by Candida parapsilosis (67%). Eighty per cent of patients (n=24) improved with antifungal therapy (fluconazole or itraconazole), and the remaining patients underwent peritoneal catheter replacement (n=3) or removal (n=3) due to persistent infection. Exit-site fungal infections were the cause of technique failure in 2 of these patients. Conclusion: Exit-site fungal infections are an unusual but important complication of peritoneal dialysis. In this study, the most relevant risk factor associated with these infections was previous antibiotherapy and the majority of patients evolving favourably under medical treatment